Climate Change Vulnerability Assessment Fortourism Sector in Ha Tinh Province - Thuy, Hoang Luu Thu; Mui, Tran Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 1, 2018)
Abstract: The vulnerability level of climate change to the tourism sector was measured by method of vulnerability assessment and adaptive capacity based on indicators proposed by the OECD. The study results in a case study of Ha Tinh province showed that: among 12 assessed district, one ranked very high; three ranked high; seven ranked average, another ranked low. The general assessment vulnerability level of tourism in Ha Tinh province caused by the impact of climate change and natural disasters was at medium level.